Characterization of a new type of mead fermented with Cannabis sativa L. (hemp). Issue 3 (8th February 2021) - Romano, Raffaele; Aiello, Alessandra; De Luca, Lucia; Sica, Rosario; Caprio, Emilio; Pizzolongo, Fabiana; Blaiotta, Giuseppe
Abstract : Abstract: Mead, one of the oldest existing drinks, is a fermented product based on honey, water, and the possible addition of spices and selected yeasts. In this work, various parts (inflorescences, leaves, and steams) of Cannabis sativa L. at different concentrations and Saccharomyces cerevisiae biotype M3/5 were added during mead fermentation. The physicochemical parameters (pH, alcoholic content, sugar content, titratable acidity, and organic acids) of the mead were assessed at the beginning and end of fermentation. Moreover, polyphenols, cannabidiol and volatile organic compounds were identified at the end of fermentation and compared with the control sample prepared without hemp and with only indigenous yeasts. The mead fermented with hemp showed the highest quantity of polyphenols (227 to 256 mg GAE/L) and a level of cannabidiol ranging from 0.26 to 0.49 mg/kg. The volatile organic compounds found were mainly alcohols, esters and terpenes, which were present at higher concentrations in the mead prepared with C. sativa L. than in the control mead and conferred freshness and "hemp aroma" characteristics. Practical Application: Inflorescences, leaves, and steams of Cannabis sativa L. were added at different concentrations during mead fermentation. This type of mead showed high quantity of polyphenols (227 to 256 mg GAE/L) and a level of cannabidiol ranging from 0.26 to 0.49 mg/kg which have anxiolytic and neuro‐protective properties. Moreover the volatile organic compounds found (mainly alcohols, esters, and terpenes) conferred freshness and "hemp aroma" characteristics.